Quantitative methods in archaeology using R - Carlson, David Lee 1952- (Cambridge, United Kingdom New York, New York Cambridge University Press, 2017)
"Quantitative Methods in Archaeology Using R is the first hands-on guide to using the R statistical computing system written specifically for archaeologists. It shows how to use the system to analyze many types of archaeological data. Part I includes tutorials on R, with applications to real archaeological data showing how to compute descriptive statistics, create tables, and produce a wide variety of charts and graphs. Part II addresses the major multivariate approaches used by archaeologists, including multiple regression (and the generalized linear model); multiple analysis of variance and discriminant analysis; principal components analysis; correspondence analysis; distances and scaling; and cluster analysis. Part III covers specialized topics in archaeology, including intra-site spatial analysis, seriation, and assemblage diversity"--Provided by publisher.
1. Organization of the book -- Part I. R and Basic Statistics -- 2. Introduction to R -- 3. Looking at data: Numerical summaries -- 4. Looking at data: Tables -- 5. Looking at data: Graphs -- 6. Transformations -- 7. Missing values -- 8. Confidence intervals and hypothesis testing -- 9. Relating variables -- Part II. Multivariate Methods -- 10. Multiple regression and generalized linear models -- 11. MANOVA and canonical and predictive discriminant analysis -- 12. Principal components analysis -- 13. Correspondence analysis -- 14. Distances and scaling -- 15. Cluster analysis -- Part III. Archaeological Approaches to Data -- 16. Spatial analysis -- 17. Seriation -- 18. Assemblage diversity -- 19. Conclusions.
Includes bibliographical references.
Keywords: Quantitative research; R (Computer program language); Archaeology -- Data processing; Archaeology -- Methodology